Evaluation of sanitary and veterinary inspection results of slaughtered sheep in Poland in 2017-2019 - Górski, Krzysztof (Array, 2021)
The aim of this study was to follow and evaluate the sanitary and veterinary inspection results of slaughtered sheep in Poland in the period 2017-2019. More than 175,000 sheep were slaughtered in Poland during this period. Post-mortem veterinary inspection revealed symptoms and/or lesions in 19,799 animals, which constituted 11.30% of all examined sheep. Of these, 134 animals (0.08%) were considered unfit for consumption. The most numerous cases were with foci of pus, contamination and congestion (5.07%) and fasciolosis (4.72%). The highest number of foci of pus, contamination and congestion in sheep carcasses were found in the Małopolskie and Podlaskie voivodeships. Most of the cases deemed unfit for consumption were found in the Podkarpackie (30), Świętokrzyskie (29) and Podlaskie (23) voivodeships, accounting for over 61% of all disqualified sheep carcasses in 2017-2019 in Poland.